“It’s the Only World We’ve Got.” Children’s Responses to Chris Jordan’s Images about SDG 14: Life Below Water - Lyndal O’Gorman (Australian Journal of Environmental Education)
Broad and complex ideas about sustainability can be communicated through the Arts. Australian curriculum documents support the integration of Arts education with education for sustainability. Responding to artworks as a viewer is a key aspect of Arts education in Australian schools. Chris Jordan is a US artist whose online media galleries communicate ideas about environmental and social justice themes. This paper reports interview data from a larger project exploring children’s responses to Chris Jordan’s artworks. Conversations were held with 28 children aged between 4 and 12 as they navigated Jordan’s website to explore the images they encountered. Data relating to SDG14: Life below water were selected for the specific focus of this paper. Thematic analysis of the data revealed five themes: connections to prior experience and knowledge, links with local contexts and places, emotional engagement with the images, solutions and action-taking and ideas related to post-humanism and the human-nature binary. These findings endorse the power of Arts-based experiences for enhancing education for sustainability in primary schools and early childhood contexts.